Regulatory T Cell Responses in Participants with Type 1 Diabetes after a Single Dose of Interleukin-2: A Non-Randomised, Open Label, Adaptive Dose-Finding Trial - Todd,J; Evangelou,M; Cutler,AJ; Pekalski,ML; Walker,NM; Stevens,HE; Porter,L; Smyth,DJ; Rainbow,DB; Ferreira,RC; Esposito,L; Hunter,KMD; et al. (PLOS Medicine, 2016)
BackgroundInterleukin-2 (IL-2) has an essential role in the expansion and function of CD4+ regulatory Tcells (Tregs). Tregs reduce tissue damage by limiting the immune response following infectionand regulate autoreactive CD4+ effector T cells (Teffs) to prevent autoimmune diseases,such as type 1 diabetes (T1D). Genetic susceptibility to T1D causes alterations inthe IL-2 pathway, a finding that supports Tregs as a cellular therapeutic target. Aldesleukin(Proleukin; recombinant human IL-2), which is administered at high doses to activate the immune system in cancer immunotherapy, is now being repositioned to treat inflammatoryand autoimmune disorders at lower doses by targeting Tregs.Methods and FindingsTo define the aldesleukin dose response for Tregs and to find doses that increase Tregsphysiologically for treatment of T1D, a statistical and systematic approach was taken byanalysing the pharmacokinetics and pharmacodynamics of single doses of subcutaneousaldesleukin in the Adaptive Study of IL-2 Dose on Regulatory T Cells in Type 1 Diabetes(DILT1D), a single centre, non-randomised, open label, adaptive dose-finding trial with 40adult participants with recently diagnosed T1D. The primary endpoint was the maximumpercentage increase in Tregs (defined as CD3+CD4+CD25highCD127low) from the baselinefrequency in each participant measured over the 7 d following treatment. There was an initiallearning phase with five pairs of participants, each pair receiving one of five preassignedsingle doses from 0.04 × 106 to 1.5 × 106 IU/m2, in order to model the doseresponsecurve. Results from each participant were then incorporated into interim statisticalmodelling to target the two doses most likely to induce 10% and 20% increases in Treg frequencies.Primary analysis of the evaluable population (n = 39) found that the optimaldoses of aldesleukin to induce 10% and 20% increases in Tregs were 0.101 × 106 IU/m2(standard error [SE] = 0.078, 95% CI = −0.052, 0.254